Webtoon Application and Sudents' Reading Activity - Syayyidina Ali; Emirati, Emirati (Universitas Cokroaminoto Palopo, 2021)
The most prominent thing to be paid attention in reading comprehension is the reading activity as well, how to stimulate and attract the students’ attention to read. The aim of this research is to investigate and describe the students’ attractiveness on the use of webtoon application in reading activity. This study was a descriptive model consisting of 35 students. It was conducted at Bulukumba Muhammadiyah University, South-Sulawesi. The data were collected with a questionnaire, it was rating scale which distributed after several meetings of treatments, and it covered 10 positive and closed statements about the use of webtoon application in reading activity and the students were asked to respond whether they are: (1) strongly agree (2) Agree (3) Undecided (4) Disagree (5) Strongly Disagree with the statements. The questionnaire was analyzed based on the percentage of each answer or response. To calculate questionnaire data into percentage, the researcher used the formula where the number of frequency is multiplied to 100% then divided to the number of the total respondents. The result of the students’ response indicated that webtoon application is interesting media used in reading activity because containing and covering electronic comics, online comics, digital comics, etc. The highest rank of the mean score is 51% of strongly agree students, 46% of agree students, 2% of undecided students, 1% of disagree students, and none of student strongly disagree to the statements on the questionnaire.